Saving Money Management pada Siswa SMA Negeri 1 Seram Bagian Barat - Parinussa, Aryance; Papilaya, Josep; Sahusilawane, Stevie (Jurnal Pengabdian Arumbai, 2025)
Students at SMA Negeri 1 Seram Bagian Barat face low financial literacy, marked by poor saving habits, lack of budgeting skills, and minimal understanding of investments. To address this, the “Saving Money Management” training was conducted to improve students’ knowledge and skills in managing personal finances in a simple, applicable way. The program aimed to build basic money management, encourage frugal living, and introduce safe investments for beginners. Using a Participatory Action Research (PAR) approach, students engaged actively in discussions, budgeting simulations, and financial tracking practices. The results showed significant improvement: understanding of money management rose by 28%, budgeting ability increased by 45%, and financial tracking habits improved by 50%. Saving habits and money allocation also increased by 50%, while knowledge of micro-investment grew by 55%. The training proved effective in enhancing financial literacy and fostering healthy financial behavior, receiving strong support from teachers and showing potential for replication in similar contexts.